Synthesis and characterization of palm oil fuel ash (POFA) and metakaolin based geopolymer for possible application in nanocoating - Khan, I.U. (American Institute of Physics Inc., 2016)
The main aim of this study was to synthesize and characterize highly amorphous geopolymer from palm oil fuel ash (POFA) and metakaolin, to be used as nanocoating. Geopolymers are man-made aluminosilicate materials that are amorphous analogues of zeolites. The geopolymers were made by condensing a mixture of raw materials metakaolin and palm oil fuel ash (POFA) with alkaline activator at a fixed ratio at room temperature. The kaolin type clay was calcined at 700°C for 4hrs to transform it into amorphous metakaolin which is more reactive precursor for geopolymer formation. The characteristics of metakaolin and geopolymers (metakaolin and palm oil fuel ash based geopolymers) were analyzed by using x-ray fluorescence (XRF), Fourier transform infra-red spectrometry (FTIR), Thermogravimetric analysis (TG/DTA) and scanning electron microscopy with energy dispersive x-ray analysis (SEM-EDX). FTIR revealed the presence of Al-O and Si-O stretching vibrations of amorphous alumino-silicate structure for metakaolin, palm oil fuel ash and geopolymers. SEM-EDX images showed the presence of reaction product complementary to NASH (N = Na2O, A = Al2O3, S = SiO2, H = H2O) solid. The resulting geopolymers that were synthesized with NaOH/Na2SiO3 solution cured at 60°C for 3 days. The results demonstrated the suitability of metakaolin and palm oil fuel ash (POFA) for synthesis of geopolymer at room temperatures. © 2016 Author(s).